(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This article explores the potential impact of Decentralized Finance (DeFi) and blockchain technology on the lending industry. By utilizing a peer-to-peer approach, DeFi can provide a more efficient, secure, and inclusive means of generating loans and conducting financial transactions. Unlike traditional banking systems, which are often slow and require extensive paperwork, a decentralized application (Dapp) can enable users to easily access loan services at any time. Additionally, the Dapp can offer lower interest rates in a transparent and secure environment. By revolutionizing the loan generation process, DeFi aims to provide users with greater flexibility, accessibility, and affordability when it comes to accessing financial services.